Partnership, and risks boycotters: theoretical approach to the impact of armed conflict in social mobilization (2014)
The central objective of this article is to build a theoretical framework to analyze the impact of armed conflict on social mobilization in local settings. To achieve this goal, three research questions are developed: how armed groups respond to collective action and organizational processes of civilians, how the state responds to the dynamics resulting from the interaction between the armed groups and civilians?, and finally, what are the consequences in terms of risk to the participants of the social mobilization groups generate conflict with their actions?